Cystatin C Is an Important Biomarker for Cardiovascular Autonomic Dysfunction in Chinese Type 2 Diabetic Patients - Xubin Yang; Qiongyan Lin; Xiaoshan Li; Lin Wu; Wen Xu; Yanhua Zhu; Hongrong Deng; Yao Zhang; Bin Yao (Journal of Diabetes Research)
Background. Cardiovascular autonomic dysfunction is closely related to increased mortality in patients with diabetes. Previous studies have proved that cystatin C (CysC) is an important predictor of both peripheral neuropathy and cardiovascular events. However, whether CysC is also associated with cardiovascular autonomic dysfunction remains unclear. Therefore, the aim of this study was to investigate the relationship between CysC and cardiovascular autonomic dysfunction in type 2 diabetic patients without renal dysfunction. Methods. A total of 161 type 2 diabetic patients with normal serum creatinine (less than 133 μmol/l) and estimated glomerular filtration rate (eGFR) higher than 60 ml/min per 1.73 m2 were recruited in our study. Cardiovascular autonomic dysfunction was determined by heart rate variability (HRV) measured by a 24-hour Holter monitor. Serum CysC was tested by particle-enhanced turbidimetric immunoassay, and subjects were divided into three groups based on the tertiles of CysC. Pearson correlation analysis was used to evaluate the association between different indexes, and the association of CysC with HRV indexes was assessed by multivariate linear regression analysis. Results. The HRV parameters were lower in the group with the highest CysC concentration than in the groups with lower levels of CysC (P<0.05). Pearson correlation analysis showed a negative relationship between CysC and the HRV parameters, including SDNN (r=−0.31, P<0.001), SDANN (r=−0.25, P=0.002), and logLF (r=−0.18, P=0.023). Furthermore, multivariate linear regression analysis revealed that CysC was independently correlated with SDNN (β=−24.11, P=0.015) and SDANN (β=−19.88, P=0.047) after adjusting for the confounding factors of gender, age, blood pressure, body mass index, eGFR, and hemoglobin A1c. Conclusions. Serum CysC levels are associated with cardiovascular autonomic dysfunction; furthermore, CysC may be a reliable and convenient biomarker for detecting cardiovascular autonomic dysfunction.